Complement Receptor Type 1 Suppresses Human B Cell Functions in SLE Patients. (17th November 2016) - Kremlitzka, Mariann; Mácsik-Valent, Bernadett; Polgár, Anna; Kiss, Emese; Poór, Gyula; Erdei, Anna
Abstract : Complement receptors (CRs) play an integral role in innate immunity and also function to initiate and shape the adaptive immune response. Our earlier results showed that complement receptor type 1 (CR1, CD35) is a potent inhibitor of the B cell receptor- (BCR-) induced functions of human B lymphocytes. Here we show that this inhibition occurs already at the initial steps of B cell activation since ligation of CR1 reduces the BCR-induced phosphorylation of key signaling molecules such as Syk and mitogen activated protein kinases (MAPKs). Furthermore, our data give evidence that although B lymphocytes of active systemic lupus erythematosus (SLE) patients express lower level of CR1, the inhibitory capacity of this complement receptor is still maintained and its ligand-induced clustering results in significant inhibition of the main B cell functions, similar to that found in the case of healthy individuals. Since we have found that reduced CR1 expression of SLE patients does not affect the inhibitory capacity of the receptor, our results further support the therapeutical potential of CD35 targeting the decrease of B cell activation and autoantibody production in autoimmune patients.